2015
DOI: 10.5897/ijnam2014.0171
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural differentials in child undernutrition in Ethiopia

Abstract: Empirical evidence on the impacts of household poverty and other socio-demographic factors regarding child undernutrition is essential in targeting resourcesMultivariate analyses showed that living in urban of Tigray and Somali regions, poor household wealth status and lack of toilet facility were the urban determinants of child underweight in Ethiopia, whereas living in rural of Gambela and Harari regions, child age of 2 and over, mother's age at first birth being 18 and under, poor and medium household wealt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Children born from parents with at least primary level of education had little chance of experiencing multiple nutritional deficiencies compared to those born from non-educated parents. The finding is consistent with earlier studies conducted in different parts of Ethiopia [39][40][41][42]. Recent studies in other parts of the world reached similar conclusion [43,44].…”
Section: Discussionsupporting
confidence: 93%
“…Children born from parents with at least primary level of education had little chance of experiencing multiple nutritional deficiencies compared to those born from non-educated parents. The finding is consistent with earlier studies conducted in different parts of Ethiopia [39][40][41][42]. Recent studies in other parts of the world reached similar conclusion [43,44].…”
Section: Discussionsupporting
confidence: 93%
“…This study also indicated that there is association between region of residence and nutritional status. Earlier survey has also shown a very low prevalence of malnutrition in these regions [ 22 ]. The watched distinction may reflect natural imperatives, more awful broad living conditions, harmful sociocultural practices, unequal intrahousehold food distribution, seasonal food insecurity, poor public facilities, and other related factors [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the majority of malnourished children were related to rural residents with low or very low social standards and these results may be due to the fact that undernutrition is strongly related to the low income and social standard and also, it is related with the rural conditions. Different authors documented that severe acute malnutrition is associated with the poor standard of living and living in rural regions [14][15][16]. The association of a higher percentage of breastfeeding with malnutrition in our study (66.7%) suggests that breastfeeding in these cases was insufficient for their normal growth which may be due to prolonged breastfeeding, breastfeeding without optimal supplementation or if the mother is weak, underweight and malnourished related to their poor socioeconomic standards and this was in agreement with Berkley et al, 2005 [17].…”
Section: Discussionmentioning
confidence: 99%